Features and clinical impact of extra-cardiac lesions with 18F-fluorodeoxyglucose positron emission tomography in patients with suspected cardiac sarcoidosis. (October 2020) - Higashi, Haruhiko; Inaba, Shinji; Iio, Chiharuko; Inoue, Katsuji; Ogimoto, Akiyoshi; Miyagawa, Masao; Mochizuki, Teruhito; Ikeda, Shuntaro; Yamaguchi, Osamu
Abstract: Background: Sarcoidosis is a systemic inflammatory disorder and can often affect any other organs beyond the heart. Whole-body 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) is used to detect not only cardiac but also extra-cardiac involvement of sarcoidosis. However, the features and clinical impact of extra-cardiac lesions have not yet been fully elucidated. Therefore, this study aimed to clarify these using FDG-PET. Methods and results: We enrolled 120 consecutive patients with abnormal findings clinically suggesting cardiac sarcoidosis who underwent whole-body FDG-PET. In this study, a patient with suspected cardiac sarcoidosis was defined as one having both clinically suspected findings and FDG-PET positive cardiac uptake. Subsequently, a total of 36 patients with suspected cardiac sarcoidosis were found and analyzed. Extra-cardiac involvement was detected in 35 lesions of 14 patients (39% per patient). In particular, the extra-cardiac lesions were widely distributed throughout the body, and mediastinal/hilar lymph node involvement was most commonly observed. In most of the patients (93% per patient, 13/14), the extra-cardiac lesions were localized in the regions that were considered more accessible with less risk of complication compared with endomyocardial biopsy (EMB). Based on the FDG-PET findings, 8 patients underwent extra-cardiac biopsy without complication, and its diagnostic sensitivity for histological sarcoidosis was high (75%, 6/8). Moreover, FDG-PET-guided extra-cardiac biopsy could confirm histological sarcoidosis in 4 lesions that EMB failed to prove. Conclusions: Extra-cardiac involvement in patients with suspected cardiac sarcoidosis was relatively high. FDG-PET-guided extra-cardiac biopsy may be safe and useful for the imaging based diagnosis of cardiac sarcoidosis.